الأنطولوجيا: النشأة والتطور والنضج - فرحة محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هذا البحث هو محاولة لإثبات أن الأنطولوجيا كانت منذ نشأتها حتى وقتنا الراهن مبحثاً في الوجود ولم تكن أبداً ميتافيزيقا وجودية, وذلك من خلال تقديم عرض تفسيري لتاريخ الأنطولوجيا, معتمداً على إعادة قراءة نصوص الفلاسفة الأنطولوجيين أنفسهم وتفسيرها, منذ الفلسفة اليونانية مروراً بالفلسفة الوسيطة والحديثة, وصولاً إلى الفلسفة المعاصرة. This article is an attempt to prove that the ontology, from its primary origin until the present time, is a study of Being, and it has never been in any time an existential metaphysics. We will try to prove this by an interpretive survey of the history of ontology, depending on the original texts of the philosophers themselves, starting from the Greek philosophy, passing through Medieval and Modern philosophy and ending at the Contemporary philosophy.